Investigating the relationship between information technology Penetration coefficient and organizational agility in the Iranian companies (Listed in Tehran stock exchange) - Hooshang Asheghi Oskooee; Moosa Azari (مدیریت مهندسی و رایانش نرم)
Organizational agility is one of new paradigms in the field of organizations management which has been presented to reward the environmental changes and satisfying the customer needs. One of the numerous factors affecting the organizational agility is to apply the Information Technology (IT). This study investigates the relationship between the IT penetration coefficient and organizational agility. This study is of type the applied research in terms of objective and it also uses survey-descriptive and correlation method in terms of nature and method. Closed questionnaire was used for examining the variables. Population is the companies accepted in Tehran Stock Exchange in 2013-14. The questionnaire and structural equation modeling were used for analyzing the obtained data and testing the hypothesis, respectively. The results obtained from data analysis indicate that the technology acceptance combination model and organization agility model are both powerful models for anticipating the organization agility and the attitude towards the use of IT has the most effect on the organization agility.